ORGANOTOXIC EFFECT OF SINGLE INTRATRACHEAL ADMINISTRATION OF LEAD NANOPARTICLES OF DIFFERENT SIZES - Gubar, I.V.; Apykhtina, O.L.; Kaminsky, R.F.; Chaikovsky, Yu.B.; Yavorovsky, O.P.; Sokurenko, L.M. (World of Medicine and Biology, 2020)
Cardiovasotoxic effect of a single intratracheal administration of lead nanoparticles of different sizes was studied in the experiment. Сolloidal solutions of lead sulfide (PbS in sodium polyphosphate) with an average size of 26–34 nm and 50–80 nm, and lead nitrate Pb(NO3)2 in ionic form which is well soluble in water were used. Toxic effects were assessed 12 days after exposure. Morphological changes were found in the myocardium and to a greater extent in the atria. Mild disorders, such as enlarged interstitial space and dystrophic changes of individual cardiomyocytes were found after administration of PbS26–34nm and Pb50–80nm nanoparticles. Thus, with intratracheal administration of lead, the toxic effect of nanoparticles PbS26–34nm and PbS50–80nm was manifested more compared with an effect caused by the action of the ionic form of lead Pb(NO3)2. The toxic effect of lead nanoparticles was mainly evident in the atrial myocardium cardiomyocytes, while the aortic wall remained almost unaffected. The most pronounced structural changes were observed in the lungs and bronchi, which may be due to the route of the toxicant administration.
Keywords: lead; nanoparticles; intratracheal intoxication; morphological changes; myocardium; aorta; lungs